1994
DOI: 10.1051/parasite/1994013219
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics of chloroquine in healthy andPlasmodium chabaudi-infected mice: implications for chronotherapy

Abstract: Summary :The schizogony of malarial parasite is a typical cyclic phenomenon where the different stages of parasite development appear at regular time intervals. Each of the stages is specifically sensitive to different antimalarial drugs. Knowledge of the details of the cycle, drug susceptibility and the pharmacokinetics of drugs, could allow the improvement of drug action by the chronotherapeutic approach: treatment at the time of appearance of the drugsensitive stage with a drug that displays rapid pharmacok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 2 publications
1
13
0
Order By: Relevance
“…Whole-blood CQ concentration was measured for the pharmacokinetic determinations, but the sampling period was only 4 h postdose, therefore limiting the findings to the distribution phase of the pharmacokinetic profile. Nevertheless, Cambie et al (11) found that malaria infection (particularly high parasitemia of Ͼ20% in mice) increased the half-life and V/F, which suggests a decreased CL/F (Tables 1 and 2). One other investigation of CQ pharmacokinetics in healthy mice has been reported, in the context of grapefruit juice interaction (4).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Whole-blood CQ concentration was measured for the pharmacokinetic determinations, but the sampling period was only 4 h postdose, therefore limiting the findings to the distribution phase of the pharmacokinetic profile. Nevertheless, Cambie et al (11) found that malaria infection (particularly high parasitemia of Ͼ20% in mice) increased the half-life and V/F, which suggests a decreased CL/F (Tables 1 and 2). One other investigation of CQ pharmacokinetics in healthy mice has been reported, in the context of grapefruit juice interaction (4).…”
Section: Discussionmentioning
confidence: 99%
“…However, pharmacokinetic data for CQ in mice were notably deficient. The only specific murine study of CQ pharmacokinetics was an investigation in healthy and malaria-infected (Plasmodium chabaudi) mice (11). Whole-blood CQ concentration was measured for the pharmacokinetic determinations, but the sampling period was only 4 h postdose, therefore limiting the findings to the distribution phase of the pharmacokinetic profile.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, stage-specific mortality caused by C cannot be involved. The half-life of whole blood Cconcentration in mice heavily infected with P. chabaudi (21-25 % parasitized RBCs) is in the order of 7 h (Cambie et al 1994). Parasite numbers were first assayed at least 2 d after treatment, when the C level must have been less than 0.5 mg kg −" ; preliminary experiments revealed twice this concentration to have no noticeable effect on parasite numbers or infection dynamics.…”
Section: Discussionmentioning
confidence: 99%